Hospital Brand Image, Patient Experience, Satisfaction dan E-Health dalam Membangun Outpatient Loyalty : [Hospital Brand Image, Patient Experience, Satisfaction and E-Health in Building Outpatient Loyalty] - Siti Shafa Indah Safira; Siti Aliyyah Akifah Korna; Safira Achriana Huda (Universitas Pelita Harapan, 2025)
Patient loyalty is an important aspect for hospitals in the face of increasingly fierce competition in the healthcare sector, especially in line with the rapid development of digital technology. This study aims to analyze the influence of hospital brand image, patient experience, patient satisfaction, and e-health on outpatient loyalty, as well as test the role of e-health as a mediator in the relationship between hospital brand image, patient experience, patient satisfaction and outpatient loyalty. This study uses a quantitative approach with a cross-sectional design. Data was collected through questionnaires distributed online to outpatients using the Mobile JKN application at Hospital X. A total of 172 respondents were selected using consecutive sampling techniques. The data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software, which included testing of measurement models and structural models. The results showed that hospital brand image and the use of e-health (JKN mobile application) had a positive and significant effect on outpatient loyalty, while patient experience and patient satisfaction showed a not significant influence on outpatient loyalty. In addition, the use of JKN mobile applications as e-health has been proven to mediate the relationship between hospital brand image and patient satisfaction with patient loyalty, but the use of e-health is not significant in mediating the relationship between patient experience and patient loyalty. Based on the results of this study, the management of RS X is recommended to strengthen the hospital brand image and optimize the integration of Mobile JKN with the hospital's internal service system to improve service efficiency, reduce waiting times, and simplify the administrative process and access to health services to build patient loyalty in the long term. Abstrak Bahasa Indonesia: Loyalitas pasien merupakan aspek yang penting bagi rumah sakit dalam menghadapi persaingan yang semakin ketat di sektor layanan kesehatan, terutama seiring dengan pesatnya perkembangan teknologi digital. Penelitian ini bertujuan untuk menganalisis pengaruh hospital brand image, patient experience, patient satisfaction, dan e-health terhadap outpatient loyalty, serta menguji peran e-health sebagai mediasi dalam hubungan antara hospital brand image, patient experience, patient satisfaction terhadap outpatient loyalty. Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Data dikumpulkan melalui kuesioner yang disebarkan secara online kepada pasien rawat jalan pengguna aplikasi Mobile JKN di RS X. Sebanyak 172 responden dipilih menggunakan teknik consecutive sampling. Data dianalisis dengan menggunakan Partial Least Square-Structural Equation Modeling (PLS-SEM) dengan bantuan software SmartPLS 4.0, yang mencakup pengujian model pengukuran dan model struktural. Hasil penelitian menunjukkan bahwa hospital brand image dan penggunaan e-health (aplikasi Mobile JKN) berpengaruh secara positif dan signifikan terhadap outpatient loyalty, sedangkan patient experience dan patient satisfaction menunjukkan pengaruh yang tidak signifikan terhadap outpatient loyalty. Selain itu, penggunaan aplikasi Mobile JKN sebagai e-health terbukti dapat memediasi hubungan antara hospital brand image dan patient satisfaction dengan patient loyalty, namun penggunaan e-health tidak signifikan dalam memediasi hubungan antara patient experience dan patient loyalty. Berdasarkan hasil penelitian ini, manajemen RS X disarankan untuk memperkuat hospital brand image dan mengoptimalkan integrasi Mobile JKN dengan sistem layanan internal rumah sakit guna meningkatkan efisiensi pelayanan, mengurangi waktu tunggu, serta mempermudah proses administrasi dan akses layanan kesehatan untuk membangun loyalitas pasien dalam jangka panjang.